Gullain-Barré Syndrome during pregnancy: Fetomaternal outcomes - Pokhrel Ghimire, Sita; Ghimire, Ram Hari; Ghimire, Ashima; Kafle, Dilliram; Chhetry, Manisha; Kumar, Mahanand (Journal of Nobel Medical College, 2016)
Background Gullain-Barré Syndrome (GBS) is not uncommon during pregnancy in our setting. There are no studies regarding the clinical profile and fetomaternal outcomes of GBS during pregnancy in Nepal. Therefore, this study was conducted to analyse clinical profile and fetomaternal outcome of pregnant women with GBS. Material & Methods Prospective descriptive analysis was carried out of all female’s cases of >16 years women of GBS with pregnancy who were admitted in the hospital between 1st August 2015 and 30th July 2016. A structured questionnaire was designed which included demographic, obstetric, clinical, neonatal and neurological parameters. Results During the period of 1 year, 11 cases were analysed with median age of 23.7 years. Disease was common in primi and in 3rd trimester. Three patients (27.2%)needed mechanical ventilation and one of them (9%) died due to ventilator associated pneumonia. There was only one (9%) neonatal death. Conclusion Gullain-Barré Syndrome is not uncommon in our setting. Early diagnosis and proper management of pregnant women with GBS may result in good fetomaternal outcome. Journal of Nobel Medical College Vol.5(2) 2016; 5-9